Sacralisation de la figure héroïque de Francisco Morazán en Amérique Centrale (1842-1942) - Catherine Lacaze (Mélanges de la Casa de Velázquez, 2016)
This article deals with the process of sacralisation of Francisco Morazán as a heroic figure, Honduran liberal and president of the Central American Federation during the 1830s. Three aspects are highlighted here, from his death in 1842 to its centennial in 1942: the development of a narrative structure taking the Christ figure as a heroic model; the conformation of a rhetoric reinforcing the sanctity of the hero; and the organisation of a civic cult to the Homeland’s demigod. This article highlights the key elements of the historical process that led to the utilisation of the hero/martyr for political ends.